Evolution of the magmatic-hydrothermal system at Lastarria volcano (Northern Chile) between 2006 and 2019: Insights from fluid geochemistry - Layana, Susana; Aguilera, Felipe; Inostroza, Manuel; Tassi, Franco; Wilkes, Thomas Charles; Bredemeyer, Stefan; González, Cristóbal; Pering, Tom David; McGonigle, Andrew John Samuel (Frontiers in Earth Science, 2023)
One of the major problems in the volcanic surveillance is how data from several techniques can be correlated and used to discriminate between possible precursors of volcanic eruptions and changes related to non-eruptive processes. Gas chemical surveys and measurements of SO2 emission rates performed in the past (2006–2019) at Lastarria volcano in Northern Chile have revealed a persistent increment of magmatic sourced gas emissions since late November 2012, following a 13 years period of intense ground uplift. In this work, we provide new insights into the gas-chemical evolution of Lastarria’s fumarolic discharges obtained from direct sampling (2006–2019) and SO2 emission rates using UV camera and DOAS instruments (2018–2019) and link these to pre-existing information on ground deformation (1998–2016) in order to determine the origin of observed degassing and ground deformation processes. We revise the four mechanisms originally proposed as alternatives by Lopez et al. (Geosphere, 2018, 14 (3), 983–1007) to explain the changes observed in the fluid geochemistry and ground deformation between 2009 and 2012, in order to explain major changes in gas-geochemistry over an extended period between 1998 and 2019. We hypothesize that a continuous sequence of processes explains the evolution in the fluid geochemistry of fumarolic discharges. Two mechanisms are responsible of the changes in the gas composition during the studied period, corresponding to a 1) deep magma chamber (7–15 km depth) pressurized by volatile exsolution (1998–2020), which is responsible of the large-scale deformation; followed by 2) a crystallization-induced degassing (2001–2020) and pressurization of the hydrothermal system (2003-early November 2012), where the former process induced the changes in the gas composition from hydrothermal-dominated to magmatic-dominated, whereas the last produced the small-scale deformation at Lastarria volcano. The changes in the gas composition since late November 2012, which were strongly dominated by magmatic volatiles, produced two consecutive processes: 1) acidification (late November 2012–2020) and 2) depletion (2019–2020) of the hydrothermal system. In this work we have shown that a long-term surveillance of the chemistry of fluid discharges provides valuable insights into underlying magmatic/volcanic processes, and consequently, for forecasting future eruptions.